The Evolution of the Free Fibula Flap for Head and Neck Reconstruction: 21 Years of Experience with 128 Flaps - Fliss, Ehud; Yanko, Ravit; Bracha, Gal; Teman, Roy; Amir, Aharon; Horowitz, Gilad; Muhanna, Nidal; Fliss, Dan M.; Gur, Eyal; Zaretski, Arik (Journal of Reconstructive Microsurgery, 2020)
Background The free fibula flap is commonly referred to as a “workhorse” for head and neck reconstruction. During our 21-year experience with this flap, we have performed several changes in preoperative planning, operative technique, and postoperative follow-up.Patients and Methods A retrospective cohort study designed to analyze the cohort of patients who underwent free fibula transfer for head and neck reconstruction. Demographics, medical background, operative data, and postoperative outcome were collected. The changes we performed in preoperative planning, operative technique, and postoperative follow-up were assessed and their impact on outcome discussed.Results During 1998 to 2019 a total of 128 free fibula flaps were transferred for head and neck reconstruction. When comparing the patients treated in the early years to those who were treated in recent years we found no statistically significant difference in minor or major nonmicrosurgical complications in the recipient and donor site and in the rate of take backs due to microsurgical reasons. However total flap failure rate improved from 28% in early years to 8% in recent years (p = 0.012).Conclusion During this 21-year period, we performed several changes in our practice. This included the use of a three-dimensional (3D) prefabricated model of the mandible, a shift toward side-table osteotomies, increasing the rate of osteofascial flaps in contrast to osteocutaneous flaps and the use of an implantable Doppler. These changes, together with a learning curve of the surgical team, significantly improved our overall success rates.
Keywords: microsurgery; head and neck; free fibula flap; mandibular reconstruction; maxillary reconstruction